Effects of Corporal Activities on Inattention and Impulsivity Hyperactivity during Non-formal Health Literacy Program - Khan, Iffat Nazir; Mahmud, Shamaila Hamid (IJLTP, 2025)
This study investigated how teenage impulsivity/hyperactivity and inattention were affected by corporal activities. It improved our comprehension of these symptoms of ADHD in light of Pakistan's increasing acknowledgment of psychological disorders as a prevalent co-occurring illness. The study emphasized the responsibilities that parents, neighbors, and the larger community played in the lives of teens with ADHD, focusing on their perceptions of sports and ADHD symptoms. Three participants, all WICA (Wasim International Cricket Academy) players in a weekend program that used non-formal education settings to test their hyperactivity/impulsivity and inattention, were examined using qualitative, descriptive, and case study methodologies. In-depth interviews were used to gather data, with a focus on teenagers with ADHD who showed heightened levels of these symptoms. The results showed that leisure time activities considerably lessened the hyperactivity/impulsivity and inattention symptoms in two out of three subjects. This study established a framework for further research and emphasized how critical it was to attend to the special requirements of teenagers with ADHD in the community.